Answers

2014-10-14T14:37:42+08:00
In solving linear equations using substitution method all you have to do is to rearrange one equation such that it may have a value in terms of the other variable.. say you have the first equation as: 2x + y = 6 
rearranging that equation you'll have the value of y in terms of x
y = -2x + 6 -----equation 3
you substitute that value attained to the second equation.. say you have the second equation as 3x + y = 10  ---equation 2
substituting equation 3 to equation 2 you'll hvae
3x + y = 10
3x -2x + 6 = 10
x = 10 - 6
x = 4
substituting the value of x in equation 3 you'll have
y = -2x + 6
y = -2(4) + 6
y = -8 + 6
y = -2
0